Cologne Consensus Conference on pulmonary hypertension - Rosenkranz, Stephan; Ghofrani, H. Ardeschir; Grünig, Ekkehard; Hoeper, Marius M. (International journal of cardiology, 2011)
Pulmonary hypertension (PH) in left heart disease, classified as group II, is the most common form of PH that occurs in approximately 60% of cases of reduced and preserved left ventricular ejection fraction. Although relatively much is known about hemodynamic stages (passive or reactive) and their consequences on the right ventricle (RV) there is no consensus on the best hemodynamic definition of group II PH. In addition, the main pathways that lead to lung capillary injury and impaired biology of small artery remodelling processes are largely unknown. Typical lung manifestations of an increased pulmonary pressure and progressive RV-pulmonary circulation uncoupling are an abnormal alveolar capillary gas diffusion, impaired lung mechanics (restriction), and exercise ventilation inefficiency. Of several classes of pulmonary vasodilators currently clinically available, oral phosphodiesterase 5 inhibition, because of its strong selectivity for targeting the cyclic guanosine monophosphate pathway in the pulmonary circulation, is increasingly emerging as an attractive opportunity to reach hemodynamic benefits, reverse capillary injury, and RV remodelling, and improve functional capacity. Guanylate cyclase stimulators offer an additional intriguing opportunity but the lack of selectivity and systemic effects might preclude some of the anticipated benefits on the pulmonary circulation. Future trials will determine whether new routes of pharmacologic strategy aimed at targeting lung structural and vascular remodelling might affect morbidity and mortality in left heart disease populations. We believe that this therapeutic goal rather than a pure hemodynamic effect might ultimately emerge as an important challenge for the clinician. - L’hypertension pulmonaire (HP) en cas de cardiopathie gauche, classifiée dans le groupe 2, est la forme la plus commune d’HP qui apparaît chez approximativement 60 % des cas de diminution ou de préservation de la fraction d’éjection ventriculaire gauche. Bien que nous en connaissions déjà beaucoup sur les stades hémodynamiques (passif ou réactif) et leurs conséquences sur le ventricule droit (VD), il n’existe aucun consensus quant à la meilleure définition du profil hémodynamique de l’HP du groupe 2. De plus, nous en connaissons très peu sur les principales voies qui mènent aux lésions des capillaires pulmonaires et à la détérioration des petits processus biologiques du remodelage artériel. Les manifestations pulmonaires typiques d’une augmentation de la pression pulmonaire et d’un découplage progressif entre le ventricule droit et la circulation pulmonaire sont une diffusion alvéolocapillaire anormale, une détérioration de la mécanique ventilatoire (restriction) et une inefficacité de la ventilation durant l’effort. Parmi les nombreuses classes de vasodilatateurs pulmonaires cliniquement disponibles en ce moment, les inhibiteurs de la phosphodiestérase de type 5 par voie orale, en raison de leur forte sélectivité à cibler la voie de la guanosine-5’-monophosphate dans la circulation pulmonaire apparaît de plus en plus comme une opportunité intéressante pour obtenir les avantages hémodynamiques, inverser les lésions capillaires et le remodelage VD, et améliorer la capacité fonctionnelle. Les stimulateurs de la guanylate cyclase offrent une opportunité additionnelle remarquable, mais le manque de sélectivité et les effets systémiques pourraient empêcher d’obtenir certains des avantages anticipés sur la circulation pulmonaire. Des essais subséquents détermineront si les nouvelles stratégies pharmacologiques ciblant le remodelage structurel et vasculaire pulmonaire pourraient effectivement influer sur la morbidité et la mortalité des populations souffrant de cardiopathie gauche. Nous croyons que cet objectif thérapeutique plutôt que de cibler seulement un effect effet hémodynamique pourrait finalement apparaître comme un enjeu important pour le clinicien. - The objective of this prospective study was to assess the efficacy of exercise training as add-on to medical therapy in patients with congenital heart disease associated pulmonary arterial hypertension (CHD-APAH). - Patients with invasively confirmed CHD-APAH received in-hospital exercise training for 3 weeks and continued at home. Efficacy parameters were evaluated at baseline, after 3 and 15 weeks. Medical treatment remained unchanged. Worsening events and survival rate were assessed in a follow-up period of 21 ± 14 months. - Twenty consecutive CHD-APAH patients (16 female, 4 male, mean pulmonary arterial pressure 60 ± 23 mm Hg) were included. Patients significantly improved the mean distance walked in 6 min compared to baseline by 63 ± 47 m after 3 weeks (p < 0.001) and by 67 ± 59 m after 15 weeks (p = 0.001). Quality of life-score (p = 0.05), peak oxygen consumption (p = 0.002) and maximal workload (p = 0.003) improved significantly by exercise training after 15 weeks. The 1- and 2‐year survival rates were 100%, the transplantation-free survival rate was 100% after 1 year and 93% after 2 years. - Exercise training as add-on to medical therapy may be effective in patients with CHD-APAH and improved work capacity, quality of life and further prognostic relevant parameters. It was associated with an excellent long-term survival. Further randomized controlled studies are needed to confirm these results.
Elektronische Reproduktion der Druckausgabe
Gesehen am 20.09.2022